The influence of organizational culture, competence and professionalism on innovative behavior, job satisfaction and performance moderated by the spiritual intelligence of Muhammadiyah university lecturers in East Kalimantan - Jafri, Mastur; Brahmasari, Ida Aju; Ardiana, I Dewa Ketut Raka (Edelweiss Applied Science and Technology, 2024)
The phenomena and problems faced by the Muhammadiyah College in East Kalimantan are still the lack of quality, performance and active role and responsibility of the lecturer, as well as to the Tri Dharma College which affects the achievement of accreditation of the study program. Objectives of this study (1) Organizational culture towards the innovative behavior of teachers of Muhammadiyah College in East Kalimantan (2) Organizational culture towards the satisfaction of the teachers in Muhammadiyah University in East Kalimantan (3) Organizational Culture towards the performance of the professors of Muhammadiyah University in East Kalimantan (4) Competence towards the innovative behavior of the faculty of Muhammadiyah University in East Kalimantan (5). Competence towards the satisfaction of professors of Muhammadiyah College in Eastern Kalimantan. (6). Competency towards the performance of teachers of Muhammadiah College in East Kalimantán. (7). Professionalism towards the innovative behavior of teachers of Muhammadiah College in the Eastern Kalimantan. (8). Professionalism towards the satisfaction of the professors of the Muhammadiyah College in East Kalimantan. (9) Professionalism towards the performance of the teachers of Muhammadiyah University in East Kalimantan. (10) Innovative behavior towards the contentment of the lecturers of the Muhammadiyah University in East Kalimantan. (11). Innovative behavior towards the performance of teachers of Muhammadiyah College in Eastern Kalimantan. (12). Satisfaction with the performances of professors of Muhammadiah College in East Kalimanton. (13). The results of this research for all hypotheses Organizational culture, competence, professional, have a positive influence on the performance of the lecturer, but have no significant impact on the Spiritual Intelligence with moderation of Innovative Behavior Against the Performance of the Lecturer.